IMPACT OF INTERNAL FACTORS IN DISTRIBUTION SOE BANK CREDIT - Atang Hermawan (Jurnal Ekonomi, 2022)
Banks are institution becoming financial _ gauge measuring strength economy a country. this _ because the bank as the party receiving the funds from Public then channel it return to Public through form credit for Upgrade wheel economy a country. For Upgrade economy so total disbursed credit must the more increase. For Upgrade distribution credit then the bank has to notice a number of factor including credit jammed, capital adequacy, as well the ability of the bank to generate profit. Study this done for test influence credit default, capital adequacy, and profitability to distribution loans to state-owned banks in Indonesia. Data used namely secondary data obtained _ from report BUMN Bank finance in the 2011-2019 period. Data analysis technique used is multiple linear regression and hypothesis test using t statistics for test regression in a manner Partial as well as the F test for for test in a manner simultaneous with level significance of 5%. Besides assumption test was also carried out classic which includes normality test, multicollinearity test, heteroscedasticity test, and auticorrelation test. Research results show that credit congested influential negative to distribution credit, capital adequacy has an effect positive to distribution credit and profitability no influential to distribution credit. Whereas in a manner simultaneous credit default, capital adequacy and profitability influential to distribution state-owned bank loans in Indonesia. Ability prediction from third variable the by 74.8%, meanwhile the remaining 25.2% is influenced by factors that are not enter to in research models.